LEVEL OF PHYSICAL CONDITIONING IN STUDENTS OF AVERAGE EDUCATION TECHNICIAN OF THE IFMS/TRÊS LAGOAS AND ITS RELATION WITH THE SUBJECT HEALTH (Fiep Bulletin - online, 2012)
The present work had as objective to carry through interventions in the area of the promotion of the health by means ofthe education for a physically active life, next to the students of Average Ensino Technician of the Federal Institute of Education,Science and Technology of the Campus Três Lagoas (IFMS/Três Lagoas). Strategies had been used so that the youngdeveloped the habit to practise physical activities. The subject allowed a reflection in the measure where the students had beenable to perceive that inadequate levels of the aerobic capacity, muscular force, flexibility and corporal fat would take theinadequate levels of related physical conditioning to the health. The students had been evaluated in the component fours of thephysical conditioning. After the evaluation the students had been guided the accomplishment of located physical exercises,walked or race and allonge. The majority of the students demonstrated a significant learning on the subject.
Keywords: physical conditioning; aerobic capacity; muscular force; flexibility and corporal fat